Dissolution-precipitation creep in polymineralic granitoid shear zones in experiments-Part 1: Strain localization mechanisms - Nevskaya, Natalia; Berger, Alfons; Stünitz, Holger; Zhan, Weijia; Ohl, Markus; Plümper, Oliver; Herwegh, Marco (Copernicus Publications, 2025)
Dissolution-precipitation creep (DPC) is considered to be one of the main processes accommodating localized strain in polymineralic shear zones of the Earth's crust. Extensive field evidence for DPC in natural shear zones supports the importance of this process. The spatiotemporal evolution and the level of compositional heterogeneity that facilitate the nucleation of such polymineralic shear zones remain poorly understood. A series of new experiments was conducted on a granitoid fine-grained (average starting grain size g1/415 μm) ultramylonite to different strains at 650 °C and 1.2 GPa, with strain rates varying from 10-3 to 10-6 s-1. In Type I experiments, a fracture was induced (prior to reaching the pressure and temperature (P-T) conditions), whereas, in Type II experiments, no initial fracture was induced. Consequently, in the Type I experiments, viscous deformation localized strictly within the previous fracture in an g1/420 μm wide zone, with grain sizes being reduced to 150-10 nm. In the Type II experiments, viscous deformation was distributed in the sample, with grain size being reduced locally to 200-50 nm. This study supports two different hypotheses for shear zone nucleation in nature. In brittle-induced strain localization, DPC will be activated and lead to a rapid and strong strain localization, producing a very weak and fast-deforming high-strain zone. In viscously induced strain localization (without main fracture), deformation concentrates in zones distributed through the sample, requiring higher shear strains to reach mechanical and microstructural steady state at slower deformation rates compared to brittle-induced strain localization. In both end-member strain localization scenarios, the dominant viscous deformation mechanism in the shear zones is grain boundary sliding combined with pinning-Assisted DPC. Our experiments indicate that chemical potentials in the microstructures in combination with different strain localization types may explain the often-observed concentration of strain in fine-grained polymineralic mylonites such as in granitoids but also other polymineralic rocks (e.g., peridotites, granulites etc.) in nature.
Keywords: Geophysics; Soil Science; Geology; Geochemistry and Petrology; Earth-Surface Processes; Stratigraphy; Palaeontology